[Rezension von: Nile Green, Islam and the army in colonial India] - Tschacher, Torsten (The journal of Asian studies, 2011)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911811001355/resource/name/firstPage-S0021911811001355a.jpg